1978
DOI: 10.1111/j.1432-1033.1978.tb12026.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Main Endonuclease Specific for Apurinic Sites of Escherichia coli (Endonuclease VI)

Abstract: The main endonuclease for apurinic sites of Eschrrichia coli (endonuclease VI) has no action on normal strands, either in double-stranded or single-stranded DNA, or on alkylated sites. The enzyme has an optimum pH at 8.5, is inhibited by EDTA and needs Mgz+ for its activity; it has a half-life of 7 min at 40 "C. A purified preparation of endonuclease VI, free of endonuclease I1 activity, contained exonuclease 111 ; the two activities (endonuclease VI and exonuclease 111) copurified and were inactivated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 26 publications
(8 reference statements)
1
53
0
Order By: Relevance
“…We found that the exonuclease III-induced nicking of urea-containing PM2 DNA was dependent on Mg2", with optimal activity between 2 and 12 mM MgCl2 (data not shown). A similar Mg2' requirement was observed when AP DNA was used as the substrate (17).…”
supporting
confidence: 66%
“…We found that the exonuclease III-induced nicking of urea-containing PM2 DNA was dependent on Mg2", with optimal activity between 2 and 12 mM MgCl2 (data not shown). A similar Mg2' requirement was observed when AP DNA was used as the substrate (17).…”
supporting
confidence: 66%
“…After incubation for 30 min at 37°C, the DNA was precipitated with ethanol (25) and dissolved in 10 mM Tris buffer (pH 8.0)-i mM trisodium EDTA. The substrates were tested by measuring the release of acid-soluble material (measured as for (15), and the preparation was dialyzed against 10 mM potassium phosphate buffer (pH 7.4) containing 1 mM trisodium EDTA. Four percent of the reduced DNA was alkali labile.…”
Section: Methodsmentioning
confidence: 99%
“…An important aspect of the action pattern of these enzymes is that they are unable to catalyze the liberation of free dRp from incised AP sites. Instead, they release dRp as part of a small oligonucleotide (15,16,39). Moreover, they do so at a reduced rate compared with excision of undamaged 5' nucleotide residues at nicks in DNA (35,39).…”
mentioning
confidence: 99%